Large artery stiffening and mortality in a rat model of early vascular remodeling induced by intrauterine growth restriction and a high‐fat diet. Issue 23 (2nd December 2022) - Mankouski, Anastasiya; Miller, Thomas A.; Dodson, R. Blair; Yu, Baifeng; Yang, Yueqin; Liu, Jingtong; Machin, Daniel R.; Donato, Anthony J.; McKnight, Robert A.; Zinkhan, Erin K.
Abstract: Intrauterine growth restriction (IUGR) and exposure to a high‐fat diet (HFD) independently increase the risk of cardiovascular disease (CVD) and hyperlipidemia. In our previous studies, IUGR increased blood pressure and promoted vascular remodeling and stiffness in early life, a finding that persisted and was augmented by a maternal HFD through postnatal day (PND) 60. The impact of these findings with aging and the development of hyperlipidemia and atherosclerosis remain unknown. We hypothesized that the previously noted impact of IUGR on hypertension, vascular remodeling, and hyperlipidemia would persist. Adult female rats were fed either a regular diet (RD) or high fat diet (HFD) prior to conception through lactation. IUGR was induced by uterine artery ligation. Offspring were weaned to either RD or HFD through PND 365. For both control (C) and IUGR (I) and rats, this resulted in the following six groups per sex: offspring from RD dams weaned to an RD (CRR and IRR), or offspring from HFD dams weaned to either an RD (CHR and IHR) or to an HFD (CHH and IHH). IHH male and female rats had increased large artery stiffness, a suggestion of fatty streaks in the aorta, and persistent decreased elastin and increased collagen in the aorta and carotid arteries. Post‐weaning HFD intake increased blood lipids regardless of IUGR status. IUGR increased HFD‐induced mortality. We speculate that HFD‐induced risk of CVD and mortality is potentiated by developmental programming of the ECM. Abstract : We report that intrauterine growth restriction impacts on early vascular aging persists and induces fatty streaks in the systemic vasculature in a rat model of maternal and offspring high‐fat diet consumption. Our study shows the importance of maternal and early life intervention to modify cardiovascular risk throughout life.